2014
DOI: 10.3138/cjhs.2744
|View full text |Cite
|
Sign up to set email alerts
|

Casual sexual relationships: Identifying definitions for one night stands, booty calls, fuck buddies, and friends with benefits

Abstract: Operational definitions of casual sexual relationships (CSRs; i.e., Friends with Benefits, Booty Call) have not been validated in previous research. In this exploratory study of terminology used to describe various CSRs, participants were provided with definitions for One Night Stand, Booty Call, Fuck Buddy, and Friends with Benefits relationships and asked to identify the corresponding label for each definition. Overall, a majority (i.e., ≥81%) of men (n=341) and women (n=544) accurately identified the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
2
24

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 53 publications
5
87
2
24
Order By: Relevance
“…Several CSREs have been the topic of study during the past decade. Prominent among these is hooking up (or hookups) and friends‐with‐benefits relationships (Bisson & Levine, ; Owen & Fincham, ), although some research has examined booty calls (e.g., Jonason, Li, & Cason, ; Jonason, Li, & Richardson, ) and fuck buddies (Wentland & Reissing, , ). Although some scholars (Wentland & Reissing, ) suggested that these CSREs potentially fall on a spectrum (as opposed to distinct experiences), these relationships have largely been studied as distinct.…”
Section: Sexual Activity In Noncommitted Relationship Contextsmentioning
confidence: 99%
“…Several CSREs have been the topic of study during the past decade. Prominent among these is hooking up (or hookups) and friends‐with‐benefits relationships (Bisson & Levine, ; Owen & Fincham, ), although some research has examined booty calls (e.g., Jonason, Li, & Cason, ; Jonason, Li, & Richardson, ) and fuck buddies (Wentland & Reissing, , ). Although some scholars (Wentland & Reissing, ) suggested that these CSREs potentially fall on a spectrum (as opposed to distinct experiences), these relationships have largely been studied as distinct.…”
Section: Sexual Activity In Noncommitted Relationship Contextsmentioning
confidence: 99%
“…College students use the term hookup to indicate a wide range of sexual behaviors, from kissing and making out, to intercourse (Bogle ; England, Shafer, and Fogarty ; Wade ). That said, the defining feature of the hookup is that participants are assumed to engage in some level of sexual activity free from the obligation to form any ongoing, committed romantic relationship (Bogle ; Wentland and Reissing ). Hookups can occur more than once between the same people, provided they share an understanding that these repeated sexual encounters do not indicate a more committed, and sexually exclusive, romantic relationship (Wentland and Reissing ).…”
Section: Hooking Up On College Campusesmentioning
confidence: 99%
“…That said, the defining feature of the hookup is that participants are assumed to engage in some level of sexual activity free from the obligation to form any ongoing, committed romantic relationship (Bogle ; Wentland and Reissing ). Hookups can occur more than once between the same people, provided they share an understanding that these repeated sexual encounters do not indicate a more committed, and sexually exclusive, romantic relationship (Wentland and Reissing ). Hookups are often arranged or pursued spontaneously at a social event or are at least expected to appear spontaneous (Wade ).…”
Section: Hooking Up On College Campusesmentioning
confidence: 99%
“…Casual sex was different than the broader behavior of hooking up which could include vaginal sex, kissing, and anything in between. Most past studies measured casual sex as either number of partners (Wentland & Reissing, 2014), last partner was casual (Eisenberg et al, 2009), or ever having casual sex (Bailey et al, 2008). Very little research had examined casual sexual behavior from a person-centered approach with a multidimensional operationalization of casual sex.…”
Section: Literature Reviewmentioning
confidence: 99%